Engagement in Digital Health App-Based Prevention Programs Is Associated With Weight Loss Among Adults Age 65+ - Auster-Gussman, Lisa A.; Lockwood, Kimberly G.; Graham, Sarah A.; Pitter, Viveka; Branch, OraLee H. (Frontiers in Digital Health, 2022)
Background: Digital health programs have been shown to be feasible and effective for the prevention of chronic diseases such as diabetes. Contrary to expectations, findings also suggest that older adults have higher levels of engagement with digital health programs than younger adults. However, there is a paucity of research examining outcomes among older adults in digital health programs and whether higher engagement is related to better outcomes. Methods: We examined weight loss outcomes for 538 users aged 65 and older participating in app-based prevention programs (i.e., the Diabetes Prevention Program and the Prevention Program) powered by artificial intelligence (AI), available on a single digital health platform. We also examined the relationship between engagement and weight loss outcomes. Results: The average weight loss was 4.51%. Greater weight loss was associated with a greater number of days with bidirectional, AI-powered coaching conversations (p<.05), more self-weighing (p<.01), and early educational lesson completion (p<.05). Conclusions: Digital health programs powered by AI offer a promising solution for health management among older adults. Older adults experienced positive health outcomes as a result of using app-based prevention programs, and higher app engagement was associated with increased weight loss.